Mathematical Uncertainty Relations and their Generalization for Multiple Incompatible Observables - Nguyen, Quang Hung (H. : ĐHQGHN, 2017)
We show that the famous Heisenberg uncertainty relation for two incompatible observables can be generalized elegantly to the determinant form for N arbitrary observables. To achieve this purpose, we propose a generalization of the Cauchy-Schwarz inequality for two sets of vectors. Simple consequences of the N-ary uncertainty relation are also discussed.